Respiratory support in the newborn - Rusepno Hassan; Imral Chair; Abdul Latief (Paediatrica Indonesiana, 1981)
The prognosis of newborn infants with acuteÂ· resplratory failure is much better in recent years, due to changes in the methods of and the indications for mechanical ventilation. Several years ago there has still hesitation to use mechanical ventilation in newborn infants. Â Stock (1973) for example suggested to reserve mechanical ventilation for patients unlikely to survive without it. It seemed that the uncertainty was due to the lack of an appropriate ventilator for newborn infants.Â